Paleoenvironmental context of the early Neanderthals of Poggetti Vecchi for the late middle Pleistocene of Central Italy. Issue 2 (30th August 2017) - Benvenuti, Marco; Bahain, Jean-Jacques; Capalbo, Chiara; Capretti, Chiara; Ciani, Francesco; D'Amico, Carmine; Esu, Daniela; Giachi, GIanna; Giuliani, Claudia; Gliozzi, Elsa; Lazzeri, Simona; Macchioni, Nicola; et al.
Abstract: Work on thermal pools at Poggetti Vecchi in Grosseto, Italy, exposed an up to 3-meter-thick succession of seven sedimentary units. Unit 2 in the lower portion of the succession contained vertebrate bones, mostly of the straight-tusked elephant, Palaeoloxodon antiquus, commingled with stone, bone, and wooden tools. Thermal carbonates overlying Unit 2 are radiometrically dated to the latter part of the middle Pleistocene. This time span indicates that early Neanderthals produced the human artifacts from Poggetti Vecchi. The elephant bones belong to seven individuals of different ages. Sedimentary facies analysis and paleoecological evidence suggest a narrow lacustrine-palustrine embayment affected by water-level fluctuations and, at times, by hydrothermal water. Cyclic lake-level variations were predominantly forced by the rapid climatic fluctuations that occurred at Marine Isotope Stage (MIS) 6–7 transition and throughout the MIS 6. Possibly an abrupt, intense, and protracted cold episode during the onset of MIS 6 led to the sudden death of the elephants, which formed an unexpected food resource for the humans of the area. The Poggetti Vecchi site adds new information on the behavioral plasticity and food procurement strategies that early Neanderthals were able to develop in Italy during the middle to the late Pleistocene transition.